INTERNET ART AS A SPECIFIC ART OF THE WEB - Berkman, Ilker; Wong, Didem Carikci; Bozkurt, Muammer (ISTANBUL KULTUR UNIV, 2017)
Our study aims to explicate the forms of artistic products which are specific to the Internet based computer technologies. Works called as Internet art were explored depending on the idea that contemporary digital art has its roots in technological art. However, traditional artefacts are out are not within the scope of this study, even they were produced via Internet technologies. The term Internet art was reframed based on a literature review. Artwork within this frame were classified as art using Internet technologies and protocols and art based on Internet oriented cultural concepts and social activities, within a historical perspective. Although this kind of classification is not an original idea of the authors, a detailed discussion was executed to clarify this idea in previous studies.
Keywords: Internet Art; Net. art; digital art; historical research; Art